AUDIT KLINIK TERHADAP PENCEGAHAN SEKUNDER STROKE DI UNIT RAWAT JALAN RUMAH SAKIT UMUM DAERAH MUNTILAN - , M.Syukri ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Stroke is still a health problem in the world and Indonesia because it is the leading cause of death in developing conutries, high prevalence and incidence, disability incurred, the cost to be incurred, and began shifting stroke at a young age. This encourages efforts to improve the management of stroke outcome. American Heart Association (AHA)/American Stroke Association (ASA) has developed a program to improve the quality of management of stroke \"Get With The Guidelines (GWTG) stroke\" which focused on the redesign of systems of stroke care in the Hospital and has been adopted by many countries including Indonesia (PERDOSSI, 2011). Although the recommendation is widespread, clinical practice guidelines only a limited effect on changing physician behavior, including the importance of guidelines on secondary prevention of stroke. Objective: This study aimed to evaluate the quality of care for secondary prevention of stroke in patients with non-hemorrhagic stroke (ischemic stroke and TIA) in clinical neurologist Muntilan Hospital Magelang regency.General Hospital. Methode: A cross-sectional survey of clinical audit with criteria and standards modification criteria and standards of Chen, et al., (2011). Modification is based on stroke guidelines PERDOSSI, 2011. Subjects were all patient records are examined and diagnosed as non-hemorrhagic stroke in the period January 1 through December 31, 2012. Surveys using the checklist, whereas analysis and improvement plan created by a team. Result and Discussion: The results showed that in the case of detection of risk factors for hypertension detection was optimal (100%). Deficiences found in the detection of diabetes risk factors 61.88%, 10.83% dyslipidemia, smoking and drinking alcohol 88.96%, and 83.75% physical activity. In terms of management, deficiences found in 38.57% statin, and 83.75% in antiplatelet/anticoagulant administration. Deficiences in control lifestyle modifications can not be assessed because the data is not available. Deficiencies in secundary pevention of stroke care target for the blood pressure 36.67% and 64.44% LDL-cholesterol. Conclusion and Suggestion: The results show that the quality of secondary prevention and secondary treatment target stroke has not been optimal. These results indicate that efforts are needed to improve the quality of secondary prevention of stroke by doctors and management in Muntilan General Hospital.